Description of a new family, new genus, and two new species of deep‐sea Forcipulatacea (Asteroidea), including the first known sea star from hydrothermal vent habitats. (May 2015) - Mah, Christopher; Linse, Katrin; Copley, Jon; Marsh, Leigh; Rogers, Alex; Clague, David; Foltz, David
Abstract : Based on a phylogenetic analysis of undescribed taxa within the Forcipulatacea, a new family of deep‐sea forcipulatacean starfishes, Paulasteriidae fam. nov., is described from deep‐sea settings. Paulasterias tyleri gen. et sp. nov. was observed at recently documented hydrothermal vents on the East Scotia Ridge, Southern Ocean. A second species, Paulasterias mcclaini gen. et sp. nov. was observed in deep‐sea settings in the North Pacific, more distant from hydrothermal vents. Both species are multi‐armed (with between six and eight arms), with a fleshy body wall, and a poorly developed or absent adoral carina. Here, we include discussions of pedicellariae morphology, feeding biology, and classification. © 2015 The Linnean Society of London